3D Porous Cu Current Collectors Derived by Hydrogen Bubble Dynamic Template for Enhanced Li Metal Anode Performance. (20th March 2019) - Qiu, Hailong; Tang, Tianyu; Asif, Muhammad; Huang, Xiaoxiao; Hou, Yanglong
Abstract: Lithium (Li) metal is the most ideal anode material for high‐energy density batteries. However, the high activity of Li metal, the large volume change, and Li dendrite formation during cycling hinder its practical application. Herein, 3D porous Cu synthesized through a simple time‐saving hydrogen bubble dynamic template method is used as a host for the improved performance Li metal anode. Contrary to the planar Cu foil, the synthesized 3D porous structure can reduce the local current density, suppress the mossy/dendritic Li growth, and buffer the volume change in the Li metal anode. Highly stable Coulombic efficiency is achieved at different specific current densities (0.5, 1, and 2 mA cm −2 ) with a capacity of 1.0 mAh cm −2 . Moreover, symmetrical Li|Li‐3D Cu cells show more stable cyclic performance with a lower overpotential even at a high current density of 3 mA cm −2 . Abstract : A 3D porous Cu foil is synthesized via the hydrogen bubble template method and characterized. The deliberately designed Cu foil with its 3D interconnected porous structure can reduce local current density to prevent Li dendrite growth and buffer volume change during Li plating/stripping processes, exhibiting stable long cycle performance: 800, 535, and 145 h at 1, 2, and 3 mA cm −2, respectively.